KOTA PADANG (Studi Perubahan Penggunaan Ruang Ekonomi Tradisional di Pasar Raya Padang Pasca Bencana 2009) - Zusmelia, Zusmelia; Firdaus, Firdaus (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Market is the most important space in economic system, especially trade. Because of its function as economicspace, market has been major interest by economic subjects both modern and traditional. More and more peopleare concerned with the market, the market economic value will be higher too, and the more and more higherthe market the market spatial dynamics will be higher too. Pasar Raya Padang is once of 15 markets on PadaCity and biggest market also with high value of economic space. Since build and known as Kampuang Jao, ithave a lot of dynamics. This research article explain the dynamics of traditional economic space after earthquake2009 at Pasar Raya Padang and the causing factors. This qualitative research at Pasar Raya Padang findthe dynamics of economic space at Pasar Raya Padang is high post-quake 2009, especially in Pasar Inpres I,II dan III, and fase VII store. Quake factor only starting point the space dynamics causes, the more factors isgovernment with them policy.